The attitude of young mathematicians – participants of KTU J. Matulionis contest – towards education methods and conditions in secondary schools - Narkevičienė, Bronė; Janušas, Giedrius (Lietuvos matematikos rinkinys, 2003)
The aim of the study is to determine how participants of KTU J. Matulionis contest evaluate the situation of education in secondary schools. Goals of the study are to determine the motives of 9–12th form students with high achievements in mathematics to participate in mathematics competitions; to distinguish essential peculiarities of education and education conditions of participants of KTU J. Matulionis contest at state, school and class level, while investigating the existing and the desirable situation; to determine how gender, school type and place of residence of a student can influence the evaluation. Conclusions: the desirable situation differs from the existing one; the possibilities of inner and outer differentiation are not fully used in work with this group of students; there are diferences depending on the gender, school type and place of residence.